Amphoteric cation exchange membrane, preparation method and application thereof, bipolar membrane and application thereof
By introducing basic monomers into the bipolar membrane to generate pyridine sulfonic acid and sulfonic acid groups, combining Donnan exclusion effect and cross-linking of acid-base groups, the problem of metal ion penetration in the bipolar membrane is solved, significantly reducing the number of metal ions in the bipolar membrane. The leakage amount of the catalyst and the hydrolysis voltage are improved, and the stability and conductivity of the membrane are improved.
Patent Information
- Application Number
- CN202411568912.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-10
AI Technical Summary
When the bipolar membrane is used for a long time in a water environment, positively charged metal ions will penetrate the cation exchange membrane, resulting in catalyst loss and product contamination. How to reduce or avoid the leakage of metal ion catalysts is a question worthy of attention.
Using zwitter cation exchange membranes, prepared from polyolefin films, styrene, divinylbenzene, alkaline monomers and benzoyl peroxide, pyridine sulfonic acid is produced by introducing basic monomers such as vinylpyridine or vinyl imidazole. and sulfonic acid groups, combined with Donnan exclusion effect, inhibit the penetration of metal ions, and increase the accumulation of molecules in the cation exchange layer through ionic cross-linking of acid-base groups to prevent catalyst leakage.
It effectively suppresses the penetration of metal ions, reduces the leakage amount of the catalyst, and reduces the hydrolysis voltage, achieving the stability and conductivity balance of the bipolar membrane.
Smart Images

Figure BDA0005119945320000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion membrane preparation, in particular to an amphoteric cation exchange membrane and a preparation method and application thereof, a bipolar membrane and application thereof. Background Art
[0002] Bipolar membrane is an ion exchange membrane composed of a cation exchange layer, an anion exchange layer and an intermediate layer. Under the action of a DC electric field, the water in the intermediate layer of the bipolar membrane will dissociate to generate hydrogen ions and hydroxide ions. The hydrogen ions pass through the cation exchange layer into the cathode chamber, and the hydroxide ions pass through the anion exchange layer into the anode chamber. The application of bipolar membranes has expanded from the chemical industry to many related international livelihood industries such as environment, resources and energy, including acid and alkali production and recovery, biological fermentation and food processing, sewage and waste metal treatment, seawater resource utilization, etc.
[0003] The most critical process in bipolar membrane electrodialysis is the dissociation of water. Introducing metal ions as catalysts into the middle layer of the bipolar membrane can greatly accelerate the rate of water dissociation. However, when the bipolar membrane is used for a long time in an aqueous environment, the positively charged metal ions will penetrate the cation exchange membrane or be adsorbed on the extremely hydrophilic sulfonic acid groups, resulting in residues on the cross section of the cation exchange membrane, causing the loss of the catalyst and product contamination. Therefore, how to reduce or avoid the leakage of metal ion catalysts is a problem worthy of attention in the application of bipolar membranes. Summary of the invention
[0004] In order to solve the above problems, the present invention provides an amphoteric cation exchange membrane and its preparation method and application, a bipolar membrane and its application. The amphoteric cation exchange membrane provided by the present invention can effectively inhibit the penetration of metal ions to cause catalyst leakage and reduce the water dissociation voltage.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides an amphoteric cation exchange membrane, which is prepared from a polyolefin membrane, styrene, divinylbenzene, a basic monomer and benzoyl peroxide;
[0007] The basic monomer includes vinyl pyridine and / or vinyl imidazole;
[0008] The polyolefin film includes a polyethylene film and / or a polypropylene film, and has a thickness of 50 to 150 μm;
[0009] The mass ratio of styrene, divinylbenzene, basic monomer and benzoyl peroxide is 86-90:8:2-6:2.5.
[0010] The present invention also provides a method for preparing the amphoteric cation exchange membrane described in the above technical solution, comprising the following steps:
[0011] 1) mixing the polyolefin film with styrene, divinylbenzene, a basic monomer and benzoyl peroxide, and soaking the film for 30 minutes to obtain a soaked film;
[0012] 2) subjecting the wetted film obtained in step 1) to a polymerization reaction to obtain a polymerized film;
[0013] 3) Immersing the polymer membrane obtained in step 2) in a sulfonation reagent to carry out a sulfonation reaction to obtain an amphoteric cation exchange membrane.
[0014] Preferably, the polymerization reaction conditions in step 2) include: temperature of 80° C. and time of 6 hours.
[0015] Preferably, the sulfonating agent in step 3) is concentrated sulfuric acid;
[0016] The conditions of the sulfonation reaction include: temperature of 70° C. and time of 48 h.
[0017] The present invention also provides the use of the amphoteric cation exchange membrane described in the above technical solution in inhibiting the leakage of metal ions from a bipolar membrane.
[0018] The present invention also provides a method for preparing a bipolar membrane, comprising the following steps:
[0019] 1) placing the gel solution on the amphoteric cation exchange membrane described in the above technical solution to form a gel layer;
[0020] 2) Placing a quaternary ammonium anion exchange membrane on the gel layer and heat pressing to obtain a bipolar membrane.
[0021] Preferably, the thickness of the gel layer in step 1) is 1 to 10 μm; the components of the gel layer include water, polyvinyl alcohol and ferric chloride, and the mass ratio of water to polyvinyl alcohol to ferric chloride is 100:2:0.4 to 0.8;
[0022] The conditions of hot pressing in step 2) include: hot pressing for 30 minutes at a temperature of 80° C. and a pressure of 5 MPa;
[0023] The thickness of the quaternary ammonium anion exchange membrane is 70-100 μm.
[0024] The present invention also provides a bipolar membrane prepared by the preparation method described in the above technical solution.
[0025] The present invention also provides the use of the bipolar membrane described in the above technical solution in inhibiting metal ion leakage.
[0026] Preferably, the metal ions include iron ions.
[0027] The present invention aims to introduce basic monomers (vinyl pyridine, vinyl imidazole) into the cation exchange layer of the bipolar membrane, that is, to prepare an amphoteric cation exchange layer containing both positive and negative groups. The addition of basic monomers such as vinyl pyridine can generate pyridine sulfonic acid under sulfonation reaction. The N atom in pyridine has a lone pair of electrons and is easy to coordinate with transition metal ions. On the other hand, due to the Donnan exclusion effect, the positively charged group (weakly basic group) can effectively inhibit the penetration of positively charged metal ions in the cation exchange layer, while the negatively charged group (sulfonate group) can ensure the required proton conductivity. The ionic crosslinking or covalent crosslinking between the acid-base groups increases the accumulation between molecules in the cation exchange layer, can effectively inhibit the penetration of metal ions to cause catalyst leakage, and reduce the water dissociation voltage.
[0028] Beneficial effects of the present invention:
[0029] The iron ion leakage of the bipolar membrane of the amphoteric cation exchange membrane provided by the invention is 0.11-0.35 mg / L, and the water dissociation voltage of the bipolar membrane is 4.8-5.8V. DETAILED DESCRIPTION
[0030] The present invention provides an amphoteric cation exchange membrane, which is prepared from a polyolefin membrane, styrene, divinylbenzene, vinylpyridine and benzoyl peroxide; the polyolefin membrane includes a polyethylene membrane and / or a polypropylene membrane, and the thickness is 50 to 150 μm; the mass ratio of the styrene, divinylbenzene, alkaline monomer and benzoyl peroxide is 86 to 90:8:2 to 6:2.5. In the present invention, the polyolefin membrane is preferably a polyethylene membrane, and the thickness is 80 to 120 μm, and the mass ratio of the styrene, divinylbenzene, alkaline monomer and benzoyl peroxide is preferably 88:8:4:2.5. The present invention does not specifically limit the source of the polyolefin membrane, and commercially available ones can be used, such as the polyethylene membrane of Zhejiang Tianyi Environmental Protection Technology Co., Ltd., which has a thickness of 120 μm.
[0031] The present invention provides a method for preparing the amphoteric cation exchange membrane described in the above technical solution, comprising the following steps:
[0032] 1) mixing the polyolefin film with styrene, divinylbenzene, a basic monomer and benzoyl peroxide, and soaking the film for 30 minutes to obtain a soaked film;
[0033] 2) subjecting the wetted film obtained in step 1) to a polymerization reaction to obtain a polymerized film;
[0034] 3) Immersing the polymer membrane obtained in step 2) in a sulfonation reagent to carry out a sulfonation reaction to obtain an amphoteric cation exchange membrane.
[0035] The present invention mixes the polyolefin film with styrene, divinylbenzene, a basic monomer and benzoyl peroxide, and impregnates the mixture for 30 minutes to obtain an impregnated film.
[0036] The present invention conducts a polymerization reaction on the obtained wet film to obtain a polymerized film. In the present invention, the polymerization reaction conditions preferably include: a temperature of 80° C. and a time of 6 hours.
[0037] In the present invention, the obtained polymer membrane is immersed in a sulfonation reagent for sulfonation reaction to obtain an amphoteric cation exchange membrane. In the present invention, the sulfonation reagent is preferably concentrated sulfuric acid. In the present invention, the conditions of the sulfonation reaction preferably include: a temperature of 70° C. and a time of 48 hours.
[0038] The present invention also provides the use of the amphoteric cation exchange membrane described in the above technical solution in inhibiting metal ion leakage of a bipolar membrane. In the present invention, the metal ion is preferably an iron ion.
[0039] The present invention also provides a method for preparing a bipolar membrane, comprising the following steps:
[0040] 1) placing the gel solution on the amphoteric cation exchange membrane described in the above technical solution to form a gel layer;
[0041] 2) Placing a quaternary ammonium anion exchange membrane on the gel layer and heat pressing to obtain a bipolar membrane.
[0042] In the present invention, the thickness of the gel layer is preferably 1 to 10 μm. In the present invention, the components of the gel layer preferably include water, polyvinyl alcohol and ferric chloride, and the mass ratio of water to polyvinyl alcohol and ferric chloride is preferably 100:2:0.4 to 0.8. In the present invention, the mass ratio of water to polyvinyl alcohol and ferric chloride is preferably 100:2:0.6. In the present invention, the ferric chloride is a water dissociation catalyst. In the present invention, the conditions of the hot pressing preferably include: hot pressing for 30 minutes at a temperature of 80°C and a pressure of 5MPa. In the present invention, the thickness of the quaternary ammonium anion exchange membrane is preferably 70 to 80 μm. In the present invention, the quaternary ammonium anion exchange membrane is preferably a commercial quaternary ammonium anion exchange membrane. In a specific embodiment of the present invention, the commercial quaternary ammonium anion exchange membrane is purchased from Shandong Tianwei Membrane Technology Co., Ltd., model TWEDA1R, with a thickness of 80 μm.
[0043] The present invention provides a bipolar membrane prepared by the preparation method described in the above technical solution.
[0044] The present invention also provides the use of the bipolar membrane described in the above technical solution in suppressing metal ion leakage. In the present invention, the metal ions preferably include iron ions.
[0045] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0046] Example 1
[0047] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 90 g styrene, 8 g divinylbenzene, 2 g vinylpyridine, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0048] 2. Take 100 mL of deionized water, add 2 g of polyvinyl alcohol and 0.4 g of ferric chloride powder, and disperse evenly by ultrasonic to form a gel solution.
[0049] 3. The gel solution was poured onto the amphoteric cation exchange layer to form a uniform layer of 5 μm, and then a commercial quaternary ammonium anion exchange membrane with a thickness of 80 μm was immediately placed thereon, and hot-pressed at 80°C and 5 MPa for 30 minutes to obtain a bipolar membrane containing an amphoteric cation exchange layer.
[0050] Example 2
[0051] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 88 g styrene, 8 g divinylbenzene, 4 g vinylpyridine, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0052] The preparation methods of steps 2 and 3 are the same as those of Example 1, and bipolar membranes with different alkaline monomer contents are obtained.
[0053] Example 3
[0054] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 86 g styrene, 8 g divinylbenzene, 6 g vinylpyridine, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0055] The preparation methods of steps 2 and 3 are the same as those of Example 1, and bipolar membranes with different alkaline monomer contents are obtained.
[0056] Example 4
[0057] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 86 g styrene, 8 g divinylbenzene, 2 g vinylimidazole, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0058] The preparation methods of steps 2 and 3 are the same as those of Example 1, and a bipolar membrane containing vinyl imidazole basic monomer is obtained.
[0059] Example 5
[0060] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 86 g styrene, 8 g divinylbenzene, 4 g vinyl imidazole, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0061] The preparation methods of steps 2 and 3 are the same as those of Example 1, and a bipolar membrane containing vinyl imidazole basic monomer is obtained.
[0062] Example 6
[0063] 1. Preparation of the amphoteric cation exchange layer: A 120 μm thick polyethylene film was used as the support layer, and was soaked in a composition of 86 g styrene, 8 g divinylbenzene, 6 g vinyl imidazole, and 2.5 g benzoyl peroxide. After 30 minutes, the film was taken out and polymerized at 80°C for 6 hours to form a base film of the amphoteric cation exchange layer. The base film was immersed in concentrated sulfuric acid and sulfonated at 70°C for 48 hours to obtain the amphoteric cation exchange layer;
[0064] The preparation methods of steps 2 and 3 are the same as those of Example 1, and a bipolar membrane containing vinyl imidazole basic monomer is obtained.
[0065] Example 7
[0066] 1. Step 1 The preparation method is the same as that in Example 1.
[0067] 2. Take 100 mL of deionized water, add 2 g of polyvinyl alcohol and 0.6 g of ferric chloride powder, and disperse evenly by ultrasonic to form a gel solution.
[0068] 3. The gel solution was poured onto the amphoteric cation exchange layer to form a 5 μm uniform layer, and then a commercial quaternary ammonium anion exchange membrane with a thickness of 80 μm was immediately placed on it and hot-pressed at 80°C and 5 MPa for 30 minutes to obtain bipolar membranes with different catalyst contents.
[0069] Example 8
[0070] 1. Step 1 The preparation method is the same as that in Example 1.
[0071] 2. Take 100 mL of deionized water, add 2 g of polyvinyl alcohol and 0.8 g of ferric chloride powder, and disperse evenly by ultrasonic to form a gel solution.
[0072] 3. The gel solution was poured onto the amphoteric cation exchange layer to form a 5 μm uniform layer, and then a commercial quaternary ammonium anion exchange membrane with a thickness of 80 μm was immediately placed on it and hot-pressed at 80°C and 5 MPa for 30 minutes to obtain bipolar membranes with different catalyst contents.
[0073] Comparative Example 1
[0074] The bipolar membrane preparation process is the same as in Example 1, except that no alkaline monomer is added.
[0075] The electrolysis performance test of the bipolar membrane prepared in the embodiment was carried out. The electrolysis test was carried out in an electrolytic cell. From left to right, a cation exchange membrane (model TWEDC1S, purchased from Shandong Tianwei Membrane Technology Co., Ltd.), a bipolar membrane prepared in the embodiment, and a cation exchange membrane (model TWEDC1S, purchased from Shandong Tianwei Membrane Technology Co., Ltd.) were arranged in the electrolytic cell in sequence. The electrolytic cell was divided into four polar chambers, which were the first, second, third, and quadrupole chambers from left to right. The first and fourth polar chambers contained 0.5M sodium sulfate solution, and the second and third polar chambers contained 0.5M sodium chloride solution. The negative electrode and the positive electrode during electrolysis were placed in the first and fourth polar chambers. Platinum titanium plates were used as electrode materials for both the positive and negative electrodes, and the positive and negative electrodes were connected to a power source through wires. The electrolysis test was conducted at 30°C, and the current density was 30mA / cm 2 The system was run for 24 hours, and the potential of the bipolar membrane was tested using a multimeter. The content of trivalent iron ions in the cathode chamber liquid was then detected according to the standard "DZ / T0064.24-2021 Groundwater Quality Analysis Method Part 24: Determination of Iron Content Thiocyanate Spectrophotometry"; the ion exchange capacity of the prepared amphoteric cation exchange membrane was determined according to the standard "HG / T6093-2022 Bipolar Membrane".
[0076] Comparative Example 2
[0077] The bipolar membrane preparation process is the same as in Example 1, except that the electrolysis test time is 48 h.
[0078] Comparative Example 3
[0079] The bipolar membrane preparation process is the same as in Example 1, except that the electrolysis test time is 72 h.
[0080] Table 1 Results of Examples 1 to 8 and Comparative Examples 1 to 3
[0081]
[0082] From Table 1, it can be concluded that the ion exchange capacity of the prepared cationic membrane by adding the basic monomer vinylpyridine or vinylimidazole is only slightly reduced compared with that without adding the basic monomer; the addition of the basic monomer has a significant improvement on the leakage of trivalent iron ions, and the leakage rate decreases with the extension of electrolysis time. Since trivalent iron ions are planted in the middle layer of the bipolar membrane, the water dissociation voltage can be effectively reduced, but too high a concentration will exceed the range of the group's force on the iron ions, resulting in an increase in leakage.
[0083] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An amphoteric cation exchange membrane, characterized in that: It is prepared from polyolefin film, styrene, divinylbenzene, basic monomer and benzoyl peroxide; The basic monomer includes vinyl pyridine and / or vinyl imidazole; The polyolefin film includes a polyethylene film and / or a polypropylene film, and has a thickness of 50 to 150 μm; The mass ratio of styrene, divinylbenzene, basic monomer and benzoyl peroxide is 86-90:8:2-6:2.
5.
2. A method for preparing the amphoteric cation exchange membrane according to claim 1, characterized in that: The following steps are involved: 1) mixing the polyolefin film with styrene, divinylbenzene, a basic monomer and benzoyl peroxide, and soaking for 30 minutes to obtain a soaked film; 2) subjecting the wetted film obtained in step 1) to a polymerization reaction to obtain a polymerized film; 3) Immersing the polymer membrane obtained in step 2) in a sulfonation reagent to carry out a sulfonation reaction to obtain an amphoteric cation exchange membrane.
3. The preparation method according to claim 2, characterized in that: The conditions of the polymerization reaction in step 2) include: temperature of 80° C. and time of 6 hours.
4. The preparation method according to claim 2, characterized in that: The sulfonating reagent in step 3) is concentrated sulfuric acid; The conditions of the sulfonation reaction include: temperature of 70° C. and time of 48 h.
5. Use of the amphoteric cation exchange membrane according to claim 1 in inhibiting metal ion leakage of bipolar membranes.
6. A method for preparing a bipolar membrane, characterized in that: The following steps are involved: 1) placing a gel solution on the amphoteric cation exchange membrane according to claim 1 to form a gel layer; 2) Placing a quaternary ammonium anion exchange membrane on the gel layer and heat pressing to obtain a bipolar membrane.
7. The preparation method according to claim 6, characterized in that: The thickness of the gel layer in step 1) is 1 to 10 μm; the components of the gel layer include water, polyvinyl alcohol and ferric chloride, and the mass ratio of water to polyvinyl alcohol to ferric chloride is 100:2:0.4 to 0.8; The conditions of hot pressing in step 2) include: hot pressing for 30 minutes at a temperature of 80° C. and a pressure of 5 MPa; The thickness of the quaternary ammonium anion exchange membrane is 70-100 μm.
8. A bipolar membrane prepared by the preparation method according to claim 6 or 7.
9. Use of the bipolar membrane according to claim 8 in suppressing metal ion leakage.
10. The use according to claim 5 or 9, characterized in that: The metal ions include iron ions.